Parâmetros agronômicos e expressão gênica associados à resistência aos fungos causadores de grãos ardidos de híbridos de milho - Paniago, Bruno da Costa (2018)
In recent years, there has been a higher incidence of spike rot and corn stalk in several Brazilian regions caused by fungi such as Fusariumverticillioides and Stenocarpellamaydis. This has caused losses of productivity and grain quality. The objectives of this proposal were: to evaluate the productivity and sanitary quality of corn hybrids, with different levels of resistance to pathogens that cause grain rot; to analyze the expression of genes associated with resistance to grain rot. Spikes of four maize hybrids being two resistant to AG7088, P4285 and two susceptible RB9077 and DKB390 were artificially inoculated with the fungi Fusariumverticillioides, and F. verticillioides and Stenocarpellamaydis, plus the control treatment with natural inoculation. The grains were harvested in two seasons. The experimental design was a completely randomized 4x3x2 factorial scheme, 4 hybrids, 3 inoculation treatments and 2 harvest seasons. The grain yield was evaluated, as well as other parameters related to the sanitary quality of the grains. The expression of heat-resistant proteins was evaluated using the electrophoresis technique. The expression of genes associated with resistance of grains to rot was evaluated using the qPCR RT technique. Greater grain yield was observed for hybrid RB9077, a hybrid classified as susceptible to fungi that cause moldy grains. There was a higher infection of the maize grains by the S. maydis fungus in the hybrids considered of low resistance, DKB390 and RB9077. Higher expression of the heat-resistant proteins was observed in the grains of the resistant hybrid P4285. There was no expression of heat-resistant proteins in the grains of the hybrids when inoculated with the associated fungi. By means of the analysis of transcripts, the LOX8 gene were more expressed in grains of the hybrid classified as resistant to the fungi that cause grain rot, P4285 compared to that observed in grains of the DKB390 hybrid classified as susceptible.